Weathering effects on the thermal conductivity of PS/PMMA blends for packaging application - H., Nahida J. (Iraqi Journal of Physics, 2019)
This work describes the weathering effects (UV-Irradiation, and Rain) on the thermal conductivity of PS, PMMA, PS/PMMA blend for packaging application. The samples were prepared by cast method at different ratios (10, 30, 50, 70, and 90 %wt). It was seen that the thermal conductivity of PMMA (0.145 W/m.K), and for PS(0.095 W/m.K), which increases by PS ratio increase up to 50% PS/PMMA blend then decreased that was attributed to increase in miscibility of the blend involved. By UV-weathering, it was seen that thermal conductivity for PMMA increased with UV-weathering up to (30hr) then decreased, that was attributed to rigidity and defect formation, respectively. For 30%PS/PMMA, there results showed unsystematic decrease in thermal conductivity, which was attributed to unsystematic degradation. By Rain-weathering, thermal conductivity PS, PMMA, and 30 %PS, PMMA, it was seen systematic decreased in PS and 30 % PS/PMMA thermal conductivity; and systematic decrease in PMMA thermal conductivity. That due to the water diffusion in the samples that created some voids, bubbles, and results in decrease in thermal conductivity. This result was attributed to the decrease in adhesive between the components of polymer systems. The results suggested that the samples involved could be used for packaging application.